Exploring the bi-directional relationship of stock return and sustainability performance through the sustainability risk lens (case of Indonesia) - Sita Deliyana Firmialy; Sudarso Kaderi Wiryono; Yunieta Anny Nainggolan (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
Sustainability investing has been evolved significantly since the last decade. The inclusion of social, environmental, and economic dimension into the portfolio screening criteria is stated as an essential strategy to increase the firms' financial performance. However, previous empirical evidence has gained a mixed result on this issue (i.e. positive, negative, and insignificant). This study contributes to the discussion by offering result on the heterogeneous effect of sustainability performance to the stock return, specifically through the sustainability risk lens. Sustainability risk is related to firm sustainability concern of not being able to perform in a